Writing a C compiler : build a real programming language from scratch - Sandler, Nora, ....- (San Francisco : No Starch Press, 2024)
An approachable, hands-on tutorial to writing a C compiler and how programming languages work. Readers are gently led step by step to build a small working compiler that continues to develop throughout the book, creating a final program that translates code written by the programmer into code the computer can understand. Writing a C Compiler offers readers an accessible, practical approach to this complex and often overly theoretical topic
Keywords: C (Computer program language).; Compilers (Computer programs).